Measurement and Prediction of the Thermal Conductivity of Tricyanomethanide- and Tetracyanoborate-Based Imidazolium Ionic Liquids - Koller, Thomas Manfred; Schmid, Stefan; Sachnov, Swetlana; Rausch, Michael Heinrich; Wasserscheid, Peter; Fröba, Andreas Paul (International Journal of Thermophysics, 2014)
The thermal conductivity of ten ionic liquids (ILs) based on the anions [C(CN)(3)](-) (tricyanomethanide) and [B(CN)(4)](-) (tetracyanoborate) carrying a homologous series of the [alkyl-MIM](+) (1-alkyl-3-methylimidazolium) cations [EMIM](+) (ethyl), [BMIM](+) (butyl) [HMIM](+) (hexyl), [OMIM](+) (octyl), [DMIM](+) (decyl) was measured by a steady-state guarded parallel-plate instrument in the temperature range between (283.15 and 353.15) K at atmospheric pressure with a total uncertainty of 5 % (k = 2). Furthermore, the refractive index required for data evaluation and the density, which is an important property in the developed prediction method for the thermal conductivity, were determined. In general, the measured thermal conductivities of the probed ILs decrease with increasing temperature and increasing alkyl-chain length of the cation. Regarding the influence of the anion, somewhat smaller values for the [B(CN)(4)](-)-based ILs compared to the [C(CN)(3)](-)-based ILs carrying the same cation are observed. Our previously developed simple prediction method for the thermal conductivity of ILs at 293.15K using only information on the molar mass and the density could be improved. By the combination of this approach with the temperature dependence of the density, an extended empirical correlation additionally describing the temperature dependence of the thermal conductivity of ILs is recommended. This correlation represents all experimental thermal-conductivity data in the literature with a standard deviation of less than 7 %.
Keywords: Density; Ionic liquids; Parallel-plate method; Prediction; Refractive index; Thermal conductivity